Análisis territorial de la Política Agraria Común (PAC) en el periodo 2014-2020. Estudio de caso: Extremadura - Francisco Manuel Martínez García; Ana Nieto Masot; Gema Cárdenas Alonso; José Manuel Pérez Pintor (Boletín de la Asociación de Geógrafos Españoles)
As Spain joined the European Union (EU), the Common Agricultural Policy (CAP) plays an important role in the agricultural sector in Extremadura with the intention of progressing a fundamental sector for the development of the regional economy and with sufficient capacity to maintain the population in rural areas. Hence, since Agenda 2000, there have been a series of reforms that have established decoupled aid by paying farmers for the environmental benefits they produce in the rural environment, as well as addressing the problems of Europe's rural areas through rural development aid. The aim of this study is to describe the latest CAP 2014-2020 budget framework in Extremadura, through a territorial analysis that has provided in-depth knowledge of the distribution of this aid. Thus, the results obtained show the concentration of the amounts in certain aids introduced in the last CAP reform, as well as how the total amounts of aid are located in the main municipalities of the region where the agricultural sector is more dynamic and concentrates a large number of farms.